The origins of the English parliament, 924-1327 The Ford Lectures delivered in the University of Oxford in Hilary term 2004 - Maddicott, John Robert (Oxford University Press, 2010)
This work is an account of the evolution of parliament. It traces the development of parliament from its earliest beginnings in the late Anglo-Saxon period to the parliament of lords and commons of the early 14th century which came to be seen as representative of the whole nation and which challenged the king in 1327.